Novel mutations in the sarcomeric protein myopalladin in patients with dilated cardiomyopathy - Meyer, Thomas (Nature Publishing Group, 2013)
Recently, missense mutations in titin-associated proteins have been linked to the pathogenesis of dilated cardiomyopathy (DCM). The objective of this study was to search for novel disease-associated mutations in the two human titin-binding proteins myopalladin and its amino-terminal-interacting partner cardiac ankyrin-repeat protein (CARP). In a cohort of 255 cases with familial and sporadic DCM, we analyzed the coding regions and all corresponding intron flanks located in the MYPN and CARP-encoding ANKRD1 gene. Two heterozygous missense mutations were detected in the MYPN gene (p.R955W and p.P961L), but neither of these mutations was found in 300 healthy controls. Both mutations were located in the α-actinin-binding region of myopalladin. Endomyocardial biopsies from the p.R955W carrier showed normal subcellular localization of myopalladin and α-actinin in cardiac myocytes, while their regular sarcomeric staining pattern was significantly disrupted in the p.P961L carrier, indicating that disturbed myofibrillogenesis and altered sarcomere assembly are the cause of the disease. In the ANKRD1 gene, we identified synonymous base exchanges (c.108T>C and c.-79C>T, respectively), but no non-synonymous mutations. In summary, we have identified novel missense mutations in the third immunoglobulin-like domain of myopalladin, which have either no or profound effects on the molecular composition of the sarcomere. According to our epidemiological data, the prevalence of ANKRD1 mutations seems to be lower than that of its binding partner myopalladin, indicating the clinical significance of myopalladin for the functional integrity of the sarcomeric apparatus and the protection against DCM.